Prevalence and causes of Leave for Health Treatment (LTS) among Military Police in the state of Ceará - Silva, Gabrielle Prudente e; Lima, Vitória Antônia Feitosa; Oliveira, Letícia de Souza; Figueiredo, Chiara Lubich Medeiros de; Santiago, Marizângela Lissandra de Oliveira; Lima, Tamires Feitosa de; Macena, Raimunda Hermelinda Maia (Seven Editora, 2023)
The work of military police (PMs) around the world involves risking their own lives in favor of defending the lives of others, implying a constant state of alert. This context, added to the work overload and the rigid relations of the corporation’s military hierarchy, can negatively affect the quality of life and health conditions of these workers. Paying attention to sick leave for health treatment is important, as work plays a fundamental role in building each individual’s identity and may be related to the causes that incapacitate workers. OBJECTIVES: To describe the prevalence and identify the main causes of sick leave (LTS). METHODOLOGY: Cross-sectional, exploratory, quantitative study, part of an umbrella project entitled "Experienced violence, health conditions and illness among civil and military police officers in the State of Ceará", carried out in 21 Military Police Battalions in the cities of Fortaleza, Quixadá, Sobral, and Canindé, in Ceará, between 2018 and 2020, with a total of 836 police officers. For data collection, a self-administered electronic questionnaire was used, using the Survey Monkey software, containing a Free and Informed Consent Form (TCLE). The analysis was performed using SPSS®20. The study was approved by COPESQ UFC Opinion No. 2,284,725. RESULTS: Most of the sample was male (91.1%), with a mean age of 39 ± 10 years, brown (70.3%), and living in a stable union (65.7%). Most reported having already taken the LTS at some point during their work at the Ceará Military Police (63.0%). the following stand out: illnesses (39.9%) and accidents (10.5%), followed by psychological issues (4%), surgeries (2.9%), and injuries (2.3%). The lower limbs are the most affected part of the body (3.5%). CONCLUSION: LTS was necessary for most PMs and its main causes show that factors internal and external to the profession may be related to the need for leave. It is concluded, therefore, that the exercise of the profession contributes to the health-illness process of these individuals, limiting the good performance of their activities and impairing their quality of life. DOI:https://doi.org/10.56238/devopinterscie-274